High Frequency Trading, it’s role in the 2007/2009 financial crisis and the 2010 flash crash - Stanley Kimani Kirika (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
High Frequency Trading (HFT) is automation of the conventional securities trades in exchanges that begins by placing limit buy or sell orders, connecting the buyer to the seller and executing the transaction for profit. HFT began in the wake of the millennium and rapidly grew till 2005, later dropping after the 2007-2009 financial crisis; igniting a huge debate. I argue that HFT neither caused the 2007-2009 financial crisis actually occasioned by mispricing of subprime mortgages nor the May 6, 2010 flash crash actually caused by the immediacy problem. That HFT is just an algorithm that attracted mistrust by a section of exchange stakeholders by reason of high speed trade execution. I finally forecast that HFT can only gain more ground after reaching its lowest in 2014, but that it requires regulation to operate in stability.